Bushen Huoxue formula attenuates lipid accumulation evoking excessive autophagy in premature ovarian insufficiency rats and palmitic acid-challenged KGN cells by modulating lipid metabolism - Li, Tian; Wei, Yao; Jiao, Beibie; Hao, Rui; Zhou, Beibei; Bian, Xinlan; Wang, Peijuan; Zhou, Yahong; Sun, Xia; Zhang, Jian (Frontiers in Pharmacology, 2024)
Introduction Premature ovarian insufficiency (POI) has affected about 3.7% of women of reproductive age and is a major factor contributing to infertility. Bushen Huoxue formula (BHF), a traditional Chinese medicine prescription, is clinically used to treat POI in China. This study aims to investigate the potential mechanisms of BHF in combating POI using corticosterone-induced rats and palmitic acid (PA)-challenged human ovarian granulosa cells (GCs). Methods Initially, ultra performance liquid chromatography tandem mass spectrometry was employed to analyze the components of BHF. The pharmacodynamic parameters evaluated included body weight, ovaries index, and serum hormone in rats. Follicle numbers were observed using H&E staining. Additionally, PCNA and TUNEL staining were used to assess GCs proliferation and apoptosis, respectively. Lipid accumulation and ROS levels were examined using Oil Red O and ROS staining. Protein expressions were determined by western blot. To probe mechanisms, cell viability and E2 levels in BHF-treated, PA-stimulated GCs were determined using MTT and ELISA, respectively. Cell apoptosis and ROS levels were assessed using TUNEL and ROS staining. Proteins related to lipid metabolism and autophagy in PA-stimulated GCs were studied using agonists. Results Our results shown that BHF effectively normalized serum hormone levels, including follicle-stimulating hormone (FSH), anti-Müllerian hormone (AMH), estradiol (E2), and luteinizing hormone (LH). Concurrently, BHF also significantly reduced follicular atresia and promoted cell proliferation while inhibiting apoptosis in POI rats. Furthermore, BHF mitigated ovarian lipid accumulation by modulating lipid metabolism, which included reducing lipid synthesis (expression of peroxisome proliferator-activated receptor γ and CCAAT/enhancer binding protein α), increasing lipid catabolism (expression of adipose triglyceride lipase), and enhancing lipid oxidation (expression of carnitine palmitoyl transferase 1A). Mechanistically, the therapeutic effects of BHF on POI were linked with alleviation of lipid deposition-induced reactive oxygen species (ROS) accumulation and excessive autophagy, corroborating the results in PA-challenged GCs. After treatment with elesclomol (a ROS inducer) and rapamycin (an autophagy inducer) in GCs, the effects of BHF were almost counteracted under model conditions. Conclusion These findings suggest that BHF alleviates the symptoms of POI by altering lipid metabolism and reducing lipid accumulation-induced ROS and autophagy, offering evidence for BHF’s efficacy in treating POI clinically.